Phenolic compounds as eco-friendly corrosion inhibitor obtained by optimized extraction from residual broccoli leaves - Luana Barros Furtado; Ricardo Costa Gomes da Silva; Wendell Faria de Oliveira; Maria José O.C. Guimarães; Gabriel Batalha Leoni; Erika Christina Ashton Nunes Chrisman; Ladimir José de Carvalho; Simone Louise Delarue Cezar Brasil; José Antônio da Cunha Ponciano Gomes (Results in Chemistry)
This study investigates the optimization of phenolic compound extraction from broccoli (Brassica oleracea) residual leaves. Through the Pareto analysis, it was identified that the ethanol-water ratio is the critical variable for maximizing phenolic content. The determined ideal conditions were 0.90 mL of ethanol per mL of water, 120 min of extraction, and 400 rpm. Notably, a 50:50 ethanolic extract exhibits superior antioxidant activity, underscoring the importance of solvent composition. Weight loss measurements (200 to 1700 ppm) at 303 to 333 K indicate increased efficiency with specific solvent proportions, with freeze-drying yielding slightly better results (95.88 %) than rotatory evaporation (89.49 %). Also, it was noticed that temperature enhances adsorption of organic compounds, with best inhibition observed at 1700 ppm, favoring improved performance. Electrochemical results indicated that the inhibitor efficiency decreases over time due to desorption, while surface characterization through confocal laser scanning microscopy confirmed reduced roughness in the presence of the inhibitor and incipient localized corrosion. Additionally, synergistic effects with intensifiers such as KI and DMSO (dimethyl sulphoxide) are noted, leading to enhanced corrosion protection (95.21 %) in aggressive acidic environments (15 % HCl). Overall, the broccoli-derived inhibitor demonstrates potential for effective corrosion inhibition for carbon steel across mild and aggressive acidic conditions.